A pulsed optical absorption spectroscopy study of wide band-gap optical materials; Optical Materials; Vol. 34, iss. 12 : Selected papers from the Third International Workshop on Advanced Spectroscopy and Optical Materials - Ogorodnikov I. N. Igor Nikolaevich (2012, 2012)
Title screen